The Effect of School Principal’s Tranformational Leadership and Teachers Occupation Perception on Teachers’ Job Satisfaction at Ayeyarwaddy International School - Htut, Aung Than (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2025)
Purpose: The purpose of this paper is to identify the effects of school principal’s transformational leadership and teachers’ occupation perception on teachers’ job satisfaction at Ayeyarwaddy International School, Mandalay, Myanmar. The objectives of the research is to examine the levels of principal’s transformational leadership attributes that include idealized influence, inspirational motivation, intellectual stimulation, and individual consideration; to examine how teachers perceive their occupation as a teacher; and to identify the effects of both examinations on teachers’ job satisfaction. The questionnaire was delivered to 117 teachers from three different school divisions – preschool, elementary school, and secondary school - and 88 teachers responded. Both the Multiple Linear Regression and Simple Linear Regression were applied for data analysis. The results revealed that school principal’s transformational leadership as well as teachers’ occupation perception has statistically significant effect on teachers’ job satisfaction. Of all the transformational attributes, the Inspirational Motivation was accounted for 28.2% of the variance in teachers’ job satisfaction and it was statistically significant at p <.001 with the Beta value of .566. Teachers’ Occupation Perception was accounted for 56.4% of the variance in teachers’ job satisfaction and it was statistically significant at p <.001 with the Beta value of .774. In conclusion, this study recommends that school principals are suggested to prioritize the inspirational motivation and intellectual stimulation and teachers to have right occupation perception to enhance teachers’ job satisfaction.